Investigation of the Impact of Two Types of Epoxidized Vietnam Rubber Seed Oils on the Properties of Polylactic Acid - Nguyen Thi Thuy; Pham Ngoc Lan (Advances in Polymer Technology)
To minimize the brittleness of polylactic acid (PLA), the epoxidized rubber seed oils (ERO) or epoxidized ester rubber seed oils (EERO) are blended with PLA. The mechanical properties of ERO bioblend are higher than that of EERO bioblend and significantly improved compared to that of the PLA sample. Elongation at break is increased by 9.1 times, and impact strength and tensile toughness improved by 139% and 1370%, respectively. The morphological study showed the microdroplets of epoxidized oils distributed in the ERO bioblend are much smaller than those in the EERO bioblend. This means that the ERO is better compatible with PLA, and both ERO and EERO are partially miscible with PLA. This compatibility is confirmed by the decrease in the glass transition temperature, Tg, from 65.7 to 60.5°C. The TGA analysis shows a sharp increase in an initial decomposition temperature (from 261.8 to 311.9°C) meaning an improvement in thermal properties. The NMR analysis proves that the epoxidized vegetable oils are linked to PLA chains, so both the melt flow index and an acid value of ERO or EERO bioblend decrease while the thermal stability is improved. The NMR peak area of some signals shows that the ERO is more attached to PLA, proving better compatibility of ERO with PLA, resulting in higher mechanical properties of ERO bioblend. The plasticizing effect of plasticizers is not dependent on the oxygen-oxirane content of the epoxidized oil but is strongly influenced by the acid value. Overall results show that both ERO and EERO can be used as a biodegradable, renewable plasticizer to replace petroleum-based plasticizers for PLA. In addition, the successful modification of PLA by using ERO or EERO promotes the use of this polymer as a potential material for researchers working on PLA applications.